Unofficial field of information and communication of ukrainian emigration in the interwar Czechoslovak Republic: anecdotes, experiences, gossip, rumors (1921-1939) - Zubko, Olga (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2021)
The article deals with informal communication between Ukrainian political emigrants, who found themselves on the territory of interwar Czechoslovaczczyna. The aim of the study. reveal a number of topics that interested Ukrainian emigrants, using such forms of informal communication as gossip, rumors, anecdotes, true and untrue stories. The methodological basis of the study is a historical-chronological method of studying the emigration everyday life, based on the study of the emergence, formation and development of norms of being and their various forms. The scientific novelty of the study is to present well-known political, social, cultural and military figures as ordinary individuals, who are characterized by the of everything ordinary and everyday, because they, first, as bearers of national identity, found themselves in new realities of life, were involved to creating and adaptation of new life rules, norms, standards, regulations of everyday life;. secondly, absorbing the realities of Czechoslovak everyday life, ukrainian emigrants transferred their previously formed "ukrainian pre-liberation" views and norms of everyday life to Czechoslovak soil. Conclusions. Informal communication in an emigration environment was indicative of relaxation of people, who often got tired of too formal norms of communication and needed changes in emotions (such as "splashing out emotions" at a football or hockey match). Escaping from some emotions, emigrants freed their psyche for others and thus emotionally rebuilt and developed.